Association between insulin resistance and sustained virologic response in hepatitis C treatment, genotypes 1 versus 2 and 3: systematic literature review and meta-analysis - Laurito,Marcela Pezzoto (2013)
BACKGROUND/AIMS: Controversial results have been found in literature for the association between insulin resistance and sustained virologic response to standard chronic hepatitis C treatment. This study aims to provide a systematic literature review with meta-analysis, in order to evaluate if insulin resistance interferes with sustained virologic response in patients infected by the HCV genotype 1 versus HCV genotypes 2 and 3, undergoing treatment with interferon and ribavirin or pegylated interferon and ribavarin. METHODS: Systematic search was performed on main electronic databases until May 2012. Primary outcome was sustained virologic response, defined as undetectable levels of HCVRNA six months after the end of treatment. Meta-analytic measure was estimated using Dersimonian and Laird's method, using Stata software. RESULTS: Thirteen studies involving 2238 infected patients were included. There was a statistically significant association between insulin resistance and lower sustained virologic response rate, and this difference occurred in HCV genotype G1 (OR: 2.23; 95% 1.59-3.13) and G2/G3 (OR: 4.45; 95% CI: 1.59-12.49). In addition, a difference was seen in the cut-offs used for defining insulin resistance by Homeostasis Model Assessment of Insulin Resistance. To minimize this limitation, sub-analysis that excluded the studies that did not use 2 as a cut-off value was performed and the results still demonstrated association between insulin resistance and sustained virologic response, for both genotypic groups. CONCLUSION: This meta-analysis provides evidence that elevated Homeostasis Model Assessment of Insulin Resistance is associated with a lower sustained virologic response rate in patients with hepatitis C treated with interferon and ribavirin or pegylated interferon and ribavarin, regardless of their genotype.